(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The prevalence of stunting in Pangkajene and Islands Regency in February 2024 showed that, of 23,576 toddlers measured, 2,046 were identified as stunted. To accelerate stunting reduction, the Family Assistance Team (TPK) was established; however, the team has faced implementation challenges that highlight the need to optimize its role and strengthen its capacity to support families more effectively. This program aimed to enhance TPK capacity by providing educational skills through a health coaching approach and by developing practical educational materials to maximize field impact. Educational media were developed in the form of a stunting-reduction handbook covering key stages of the life course, including preconception, pregnancy, the postpartum period, and early childhood. In addition, the TPK Team participated in health coaching training supported by an ISBN-registered health coaching book. Following the training, mentoring sessions were conducted, and the TPK Team subsequently carried out home visits to targeted families. The results demonstrated a substantial improvement in the team’s knowledge, with mean pre-test scores of 78.70 increasing to 94.05 on the post-test and reaching 100% in subsequent assessments. The findings also indicated increased confidence among TPK members in assisting stunting-targeted families using a health coaching approach. The educational handbook is expected to be actively utilized as a core reference in routine mentoring activities. Overall, the TPK Team perceived the initiative as highly beneficial and reported gaining new insights for supporting target families. Going forward, the team is encouraged to sustain family mentoring using health coaching principles and to fully integrate the developed handbook into their service delivery. — Prevalensi stunting di Kabupaten Pangkajene dan Kepulauan pada Februari Tahun 2024 menggambarkan bahwa terdapat 23.576 balita yang diukur dan 2046 diantaranya mengalami stunting. Tim TPK dibentuk untuk membantu percepatan penurunan stunting. Namun, tim ini masih mengalami kendala dalam implementasinya oleh karena itu diperlukan optimalisasi peran tim TPK dengan meningkatkan kemampuannya dalam mendampingi keluarga. Tim TPK perlu dibekali kamampuan edukasi dengan pendekatan health coaching serta penyediaan media edukasi untuk mengoptimalkan perannya. Kegiatan ini dilaksanakan dengan penyediaan media edukasi berupa buku materi edukasi percepatan stunting untuk semua sasaran yaitu mulai masa prakonsepsi, ibu hamil, ibu nifas, dan balita. Selanjutnya dilakukan pelatihan health coaching bagi tim TPK yang dilengkapi dengan penyediaan buku ber-ISBN tentang health coaching. Setelah pelatihan dilakukan Pendampingan health coaching bagi tim TPK dan TPK melakukan Home Visit. Hasil kegiatan menunjukkan terjadi peningkatan pengetahuan TPK pada saat pelatihan yaitu dari 78.70 pada pre-test menjadi 94.05 pada post-test dan 100%. Hasil lain menunjukkan bahwa tim TPK percaya diri untuk dapat melakukan pendampingan pada sasaran stunting dengan menggunakan pendekatan health coaching dan buku yang telah disediakan akan digunakan oleh tim TPK. Tim TPK memberikan kesan bahwa kegiatan ini sangat bermanfaat dan memberikan pandangan baru dalam mendampingi keluarga sasaran. Selanjutnya, tim TPK dapat melanjutkan kegiatan pendampingan dengan menggunakan pendekatan ini dan memanfaatkan buku yang telah dibuat tim.